Персонал організації як складова її стабільної діяльності - Петрова, І. А.; Petrova, I. A. (Право і безпека. - 2013. - № 2 (49). - С. 161-165, 2013)
Статтю присвячено питанням виявлення небезпеки діяльності організації з боку власного персоналу. Проаналізовано особливості виявлення джерел такої небезпеки та визначено їх основні характеристики. Дано характеристику заходів щодо підтримки рівня економічної безпеки залежно від дії дестабілізаційних факторів з боку власних працівників. Конкретизовано структуру кадрової політики організації, її основні елементи, що дозволяють забезпечити стабільну діяльність організації, запропоновано основні індикатори та ознаки, характерні для потенційних правопорушників із персоналу організації.

The article is devoted to the problems of revealing the danger for organization’s activity from its staff. The features of revealing such sources of danger are analyzed; their main characteristics are determined. The organization can be damaged by its own staff by means of goods plundering, fraud, misuse of internal resources, dissemination of privileged information, etc. These are the main types of threats of stable organization’s existence and safety from its own employees. Characteristic of measures concerning maintaining economic security level related to action of destabilizing factors from its own employees is presented. One of these measures is guaranteeing security of organization’s employees, especially heads of all levels of management that is granted by another security unit. While working with the organization’s staff the heads should check not only keeping trade secret and values by the employees, but also their attitude to office duties, accuracy while working with documents, extra «interest» to other departments. The main measure is an organized, consecutive and purposeful personnel policy that is effectively realized through the modern technologies of personnel administration. The structure of personnel policy, its main elements that allow ensuring stable activity of organization is specified. Personnel policy consists of a number of elements that include professional selection of personnel, examination of candidates, newcomers’ training to the specifics of the work, creating proper work conditions, determination of the terms of moral and financial stimulation, care about professional growth and promotion, creation of healthy moral and psychological climate, development of criteria of work load and estimation of the results, development of employees’ inspection system, etc. The main indicators for revealing certain employees, who perpetrate divulgation of confidential information, steal money or commit other illegal acts threatening the company’s economic state, are offered for the heads.

Статья посвящена вопросам выявления опасностей деятельности организации со стороны собственного персонала. Проанализированы особенности выявления источников такой опасности и определены их основные характеристики. Дана характеристика мероприятий по поддержанию уровня экономической безопасности в зависимости от действия дестабилизирующих факторов со стороны собственных работников. Конкретизирована структура кадровой политики организации и её основные элементы, которые позволяют обеспечить стабильную деятельность организации, предложены основные индикаторы и признаки, характерные для потенциальных правонарушителей из персонала организации.
Organization’s staff as a component of its stable activity
Персонал организации как составляющая её стабильной деятельности
Keywords: організація; персонал; економічна безпека; кадрова політика; стабільна діяльність; джерела небезпеки; organization; staff; economic security; personnel policy; stable activity; sources of threat; организация; экономическая безопасность; кадровая политика; стабильная деятельность; источники опасности